How do tax incentives affect business investment? Evidence from German bonus depreciation - Sebastian Eichfelder; Kerstin Schneider (Arbeitskreis Quantitative Steuerlehre (arqus), 2018)
We analyse how tax incentives in the form of accelerated depreciations ("bonus depreciation") affect business investment. By exploiting exogenous variation in tax regulation of a regional bonus depreciation program in the former East Germany, we identify and quantify the impact from bonus depreciation on building and equipment investments at the extensive and intensive margins in the German manufacturing industry. We observe a stronger response for building investments and from large firms. There is only weak evidence of subsidy shopping but stronger evidence of investment shifting to years with more generous bonus depreciation regulations.
Keywords: G11; H25; H32; M41; 330; bonus depreciation; tax incentive; business taxation; heterogeneity